THE CORRELATION BETWEEN PLASMA D-DIMER LEVEL AND LESION VOLUME IN ACUTE ISCHEMIC STROKE - Noor, Amina; Mustafa, Hassan; Ali, Syed Affan; kazmi, Sumera; Noor, Nasma; Malik, Saqib (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out correlation between serum D-dimer and lesion volume in acute ischemic stroke. Methodology: This cross-sectional study was conducted in Ayub Teaching Hospital, Abbottabad from April 2018 to December 2018. A total of 83 patients with ischemic stroke were enrolled in this study using non-probability consecutive sampling. Diagnosis was made on history, examination and computerized tomography (CT) brain findings. A pre-designed proforma was used to collect data, which was analyzed using SPSS version 20. Descriptive and inferential statistics were applied where needed. Results: Out of 83 patients, the mean age was 52.78 ± 10.37 years with range from 35 to 65 years. In total, 64 (77.11%) were males. Infarct volume on CT ranged from 18.00 to 192.00 cc with mean of 74.10 ± 35.02 cc. Plasma D-dimer level ranged from 10 to 200 µg/l with mean of 80.23 ± 54.65. Gender stratification of age, infarct volume and plasma D-dimer in male revealed means of 53.41 ± 10.30, 74.01 ± 34.98, and 82.20 ± 55.64 respectively, while in females means were recorded as 50.68 ± 10.58, 74.42 ± 36.11, and 73.58 ± 52.08 respectively. The correlation statistics, between infarct volume and plasma D-dimer level revealed significant positive correlation (r=0.537; p=<0.001). Correlation was further stratified based on gender and a significatly positively corelation coefficient was found. Conclusion: Significant positive correlation was found between plasma D-dimer and lesion volume in acute ischemic stroke.